Influence of Space Weather on the Reliability of the Transport System Functioning at High Latitudes - Pilipenko Vyacheslav; Chernikov A. A.; Soloviev Anatoly; Yagova Nadezda; Sakharov Yaroslav; Kudin Dmitriy Vladimirovich; Kostarev Danila; Kozyreva Olga; Vorobev A.; Belov Anatoliy (Russian Journal of Earth Sciences)
The review offered for the first time in the Russian scientific literature is devoted to various aspects of the problem of the impact of space weather on ground transport systems. An analysis of available information indicates that space weather disturbances can affect rail infrastructure through both direct and indirect effects on system components. One of the main hazards is geomagnetically induced currents (GICs) in grounded extended structures excited by the geomagnetic field disturbances. The telluric electric fields and currents associated with them can cause power outages and malfunctions in the railway automation track circuits. Indirect impact is possible through disturbances in the stable supply of electricity, disturbances in communication systems and in the appearance of positioning errors in global navigation satellite systems. The review provides information necessary for engineers of transport and energy systems about the main factors of space weather that could pose a threat to such systems. Examples of the influence of geomagnetic disturbances on the automatic signaling of the northern sections of Russian Railways are given. The prospects for monitoring space weather and the aurora oval for the needs of Russian Railways are discussed.